Party platforms in electoral competition with heterogeneous constituencies - Thomas Kittsteiner; Erik Eyster (Theoretical Economics, 2007)
This paper shows how political parties differentiate to reduce electoral competition. Two parties choose platforms in a unidimensional policy space, and then candidates from these parties compete for votes in a continuum of constituencies with different median voters. Departing from their parties' platforms is costly enough that candidates do not take the median voter's preferred position in every constituency. Because the candidate whose party is located closer to the median voter gets a higher expected payoff, parties acting in their candidates' best interests differentiate—when one party locates right of center, the other prefers to locate strictly left of center to carve out a "home turf,'' constituencies that can be won with little to no deviation from the platform of the candidate's party. Hence, competition that pulls candidates together pushes parties apart. Decreasing "campaign costs'' increases party differentiation as the leftist party must move further from the rightist party to carve out its home turf, as does increasing heterogeneity across constituencies.
Keywords: C72; 330; Political parties; median voter; Hotelling competition